Percentile Norms for an Early Reading Assessment in Malay - Julia Ai Cheng, Lee; Seung Jin, Lee; Puay Hoon, Ong; Zaimuariffudin Shukri, Nordin; Nur Fatihah, Mat Yusoff (UNIMAS Publisher, 2022)
The study aimed to develop percentile norms on early reading proficiency among young elementary school children. These percentile norms were derived from a suite of early reading assessments in Malay administered to 866 Primary One (Grade 1 equivalent) school children from multilingual and multi-ethnic backgrounds. During testing, the children (462 males and 404 females) were approximately seven years old. The early reading assessment battery included measures such as letter writing, letter name knowledge, letter name fluency, rapid automatised naming, phonological awareness comprising elision, phonological memory, spelling, word reading accuracy, word reading efficiency, oral reading fluency, reading comprehension, vocabulary comprising expressive vocabulary and receptive vocabulary, and listening comprehension. These percentile norms are useful for the early identification and intervention of young children with reading difficulties and reading disabilities from multilingual communities whose languages include Malay, a transparent orthography. The implications of using the norms data for the diagnosis and classification of children with reading difficulties are discussed.